Management challenges and therapeutic strategies for metastatic melanoma – a case report - Aglio, Andrea M.; Cracchiolo, Salvatore; Impellizzeri, Giuseppe; Górecki, Michał (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. This case report focuses on a 26-year-old female with metastatic melanoma. It highlights the diagnostic process, initial immunotherapy, disease progression, and successful response to second-line therapy. Emphasizing the importance of early detection, personalized treatment, and adaptive strategies, it provides valuable insights into managing this aggressive form of skin cancer. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. A 26-year-old Caucasian female presented with a suspicious pigmented lesion on her thigh in 2013. The lesion was confirmed as superficial skin melanoma. No lymph node biopsy was performed. In 2021, she had abdominal pain and imaging revealed melanoma metastasis in the peritoneum, lungs and brain. Genetic testing showed BRAF V600E mutation and PD-L1 expression in tumor cells. She received immunotherapy and radiation for a central nervous system metastases but developed a brain hematoma. Follow-up imaging showed disease progression. She started second-line therapy with iBRAF/iMEK, and her condition rapidly improved with regression of metastatic lesions. Follow-up imaging confirmed significant positive changes and almost complete regression of neoplastic lesions. She continues to receive the targeted therapy and shows a positive response. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Early diagnosis improves outcomes in metastatic melanoma. Peritoneal metastases should be considered in patients with abdominal symptoms. The combination of gamma knife radiosurgery with immunotherapy or targeted therapy shows promise for managing brain metastases, but careful patient selection and monitoring are vital due to potential risks. Treatment responses in advanced melanoma vary, with this case highlighting a favorable response to BRAF/MEK inhibitor therapy in a patient with a BRAF gene mutation. Further research and clinical trials are needed to refine treatment approaches and improve outcomes in metastatic melanoma.